The Hybrid Languages of Love and Comics. - Nguyen, Trung Lê; Yang, Gene Luen (World Literature Today)
The article presents the author's views on enjoying learning English alongside immigrant parents, emphasizing the importance of children's literature in their multilingual household. It mentions their journey into comics, highlighting the industry's challenges in the '90s and the turning point with the success of "American Born Chinese," advocating for a deeper appreciation of art and the bonds formed through shared passions.